Multidimensional training among Latin America's restoration professionals - Meli, P.; Schweizer, D.; Brancalion, Pedro H.S.; Murcia, C.; Guariguata, Manuel R. (Wiley, 2019)
The ambitious restoration commitments made by Latin American countries have increased the demand for professionals having multidimensional training in ecological restoration; however, little is known about the kind of training that professionals are currently receiving. Through an online survey, we explored whether restoration professionals in Latin America have been trained on the ecological, socioeconomic, and management dimensions of ecological restoration, and their perceptions of training constraints and curricula needs. Half of the 411 respondents simultaneously work in academia, governments, and nongovernmental organizations, lessening the typical division between the science and practice of restoration, and suggesting the need for stronger multidimensional training to adequately respond to different needs and expectations. Over 80% received formal academic training in fields relevant for restoration and most respondents also reported attending interdisciplinary courses. Training was more focused on the ecological dimension of restoration compared to socioeconomic or management dimensions. Respondents have similar education levels (i.e. most respondents have postgraduate degrees), independently from the organization type in which respondents work, and multidimensionality among organization types was slight. Professionals expressed a need for training opportunities not demanding full‐time dedication. Although increasing training opportunities in socioeconomic and management dimensions is needed, we highlight opportunities to reinforce multidimensional training on restoration through organizational and institutional training, and collaborations among organizations.